Analysing Contemporary Metropolitan Spatial Plans in Europe Through Their Institutional Context, Instrumental Content and Planning Process. Issue 1 (2nd January 2016) - Elinbaum, Pablo; Galland, Daniel
Abstract: This article sets out to propose and apply a qualitative framework for thinking about how to analyse and compare metropolitan spatial plans in a milieu of divergent spatial planning traditions and discretionary planning practices. In doing so, the article reviews and develops an understanding concerning the institutional context, instrumental content and planning processes associated with four contemporary metropolitan spatial plans in Europe, namely those of London, Copenhagen, Paris and Barcelona. Through the results of a multiple case study and a subsequent cross-comparative analysis, the article stresses that contemporary metropolitan spatial plans tend to merge the characteristics associated with project-based and strategy-based spatial plans, thus contrasting with the typical land-use character of municipal plans and the often strategic, growth-oriented pursuit of regional plans in Europe. In this sense, the metropolitan scale is treated less explicitly as a planning scale per se; rather, it tends to emerge as a "concealed" scale between municipal and regional scales and also between local and regional knowledge in planning. Moreover, the analysis suggests that while metropolitan plans seem to converge in terms of their general themes, they cannot be ultimately "typified" in view of ad hoc variations related to their institutional contexts, instrumental contents and planning processes.